Optimization of a model of out-of-hospital antibiotic therapy (OPAT) in a Belgian university hospital resulting in a proposal for national implementation. Issue 5 (2nd September 2016) - Ravelingien, Tine; Buyle, Franky; Deryckere, Sabine; Sermijn, Erica; Debrauwere, Mieke; Verplancke, Katleen; Callens, Steven; Commeyne, Sabrina; Pattyn, Christophe; Vogelaers, Dirk
Abstract : Objectives: Some infections require prolonged parenteral antimicrobial therapy, which can be continued in an outpatient setting. The Ghent University Hospital has 15 years of experience with Outpatient Parenteral Antimicrobial Therapy (OPAT) in the home setting of the patient. Methods: Multidisciplinary critical approach through identification of areas for improvement with the existing OPAT process within the Ghent University Hospital. Existing literature and guidelines were used as references. An improved model is proposed for implementation. Results: Several challenges and barriers were identified, including regulatory obstacles for OPAT in Belgium, such as lack of uniformity in ambulatory reimbursement of parenteral antimicrobials. There is no financial incentive for the patient with OPAT, as costs for the patient of outpatient therapy can be higher as compared with hospitalization. Other barriers include delayed approval of the certificate for reimbursement, low availability of medicines in the community pharmacies and limited knowledge of the medical devices for administration in ambulatory setting. All critical steps in the revised OPAT program are summarized in a flowchart with a checklist for all stakeholders. Firstly, a list with specific criteria to include patients in an OPAT program is provided. Secondly, the Multidisciplinary Infection Team received a formal mandate to review all eligible OPAT patients. In order to select the most appropriate catheter, a decision tree was developed and standardized packages with medical devices were developed. Thirdly, patients receive oral and written information about the treatment with practical and financial implications. Fourthly, information is provided toward the general practitioners, community pharmacist and home care nurse. Conclusion: Standardization of the OPAT program aims at improving quality and safety of intravenous antimicrobial therapy in the home setting.